Evaluating an English for Specific Purposes Course for Law Students - Acosta Salazar, Ana Yeraldín (2015)
This article describes a supervised practice which was focused on creating and teaching an English for Specific Purposes course for law students. This course was based on the needs, wants, and lacks of the population. These aspects were previously identified by interviewing professionals in the area and carrying out a diagnostic test and a questionnaire to know the main interests of the population in using English for occupational purposes. The methodology used to teach the classes was task-based instruction; the students had to perform tasks like participating in a job interview and communicating orally and in written form with potential clients. From the main results, it can be concluded that the course was successful in preparing the students to perform the target tasks.